Performance of Different Rice (Oryza sativa L.) Cultivars under Aerobic Conditions - Neelima, S.; Kumar, K. Ashok (International Journal of Bio-resource and Stress Management, 2011)
Low land rice, the traditional rice growing practice, requires high water input and is being under threat due to increasing scarcity of fresh water under wet land eco-system that warrants new water saving rice cultivation. Aerobic rice cultivation offers an opportunity to produce rice with less water. In aerobic rice system, fields remain un-flooded throughout the season like an upland crop and is grown in un-puddled, aerobic soils under irrigation and high external inputs. Hence, there is a need to evaluate the existing rice varieties that are suitable for aerobic cultivation. Twelve rice entries were evaluated along with three checks in direct sown, un-puddled irrigated conditions in the scarce rainfall zone of Andhra Pradesh. Among the different rice cultivars tested, MTU 4870 recorded higher grain yield (4.8 t ha-1) over all other cultivars but was on par with RDR 1010 (4 t ha-1), RDR 977 (3.9 t ha-1) and RDR 996 (3.8 t ha-1)